Economic transformation, altered nutritional habits and health implications in Russia - Christine Burggraf; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2016)
The obesity crisis proclaimed by the World Health Organization, along with all its health consequences, started in the Russian Federation at the beginning of the millennium. This fact is gaining increasing significance against the background of the "tax on unhealthy foods" that is currently being discussed in Russia and is the result of changing lifestyle and nutritional habits. Rising economic growth and private incomes in Russia have brought about an increase in the consumption of high-fat animal products, and the health of many citizens is jeopardized by an increased risk of adiposity and diet-related chronic diseases. At the same time, health-related diets have improved in terms of vitamin and mineral intake. These two opposing developments are typically also found in other industrial and emerging economies, though in a more distinctive form in the Russian Federation. The underlying reasons appear to be traditionally rather high preferences for high-fat animal products in Russian society, but also, similar to many other countries, inadequate nutrition information. Hence, better-targeted information campaigns and clear product labelling could pave the way to healthier eating.
urn:nbn:de:gbv:3:2-113071
Keywords: 330